Dampak Kecerdasan Buatan (AI) terhadap Produktivitas dan Efisiensi Operasional Perusahaan - Amelia Ismiani; Audra Nur Fatimah; Sellia Aura Mumtaza; Sri Mulyeni (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The rapid growth of Artificial Intelligence (AI) has become a major driver of digital transformation across industries. This study aims to examine how AI adoption affects employee productivity and operational efficiency, while also identifying challenges in its implementation. Using a qualitative descriptive method through a literature review of scientific journals from Google Scholar, the findings show that AI integration brings significant benefits, such as faster work through task automation, reduced human error, and more accurate data-driven decision-making. However, challenges remain, including high integration costs, data security risks, cyber threats, and employee resistance due to digital skill gaps or the technology adoption paradox, where technological advances do not always directly increase productivity. In conclusion, the success of AI implementation depends not only on technological sophistication but also on human resource readiness, making continuous training (upskilling and reskilling) and effective change management essential to foster collaboration between artificial intelligence and human adaptability.